2001
DOI: 10.1038/sj.bjp.0704030
|View full text |Cite
|
Sign up to set email alerts
|

Sibutramine reduces feeding, body fat and improves insulin resistance in dietary‐obese male Wistar rats independently of hypothalamic neuropeptide Y

Abstract: 1 We studied the eects of the novel noradrenaline and serotonin (5-HT) reuptake inhibitor sibutramine on feeding and body weight in a rat model of dietary obesity, and whether it interacts with hypothalamic neuropeptide Y (NPY) neurones. 2 Chow-fed and dietary-obese (DIO) male Wistar rats were given sibutramine (3 mg kg 71 day 71 p.o.) or deionized water for 21 days.3 Sibutramine decreased food intake throughout the treatment period in both dietary-obese rats (P50.0001) and lean rats (P50.0001). Weight gain wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
5
16

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 45 publications
2
29
5
16
Order By: Relevance
“…Conversely, sibutramine increases energy expenditure (Hansen et al 1998(Hansen et al , 1999, and in the current study, sibutramine decreased the discriminative stimulus effects of 22-h food deprivation. Future studies will examine the potential interaction between agents that produce discriminative stimulus effects of 22-h deprivation and agents that decrease these effects, although previous studies have indicated that these compounds can work independently (Brown et al 2001). In sum, these results indicate that the assessment of the discriminative stimulus effects of acute food deprivation may be a useful behavioral model to identify potential pharmacotherapies for obesity and other eating-related conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, sibutramine increases energy expenditure (Hansen et al 1998(Hansen et al , 1999, and in the current study, sibutramine decreased the discriminative stimulus effects of 22-h food deprivation. Future studies will examine the potential interaction between agents that produce discriminative stimulus effects of 22-h deprivation and agents that decrease these effects, although previous studies have indicated that these compounds can work independently (Brown et al 2001). In sum, these results indicate that the assessment of the discriminative stimulus effects of acute food deprivation may be a useful behavioral model to identify potential pharmacotherapies for obesity and other eating-related conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, a 0.25 mg/ml solution of PYY(3-36) was prepared in saline and stored at 37°C. From this solution, samples were taken at days 1,3,7,8,10,11,14,16,18,21,23, and 25. Degradation was stopped by precipitation of sample with 10 l of 50:50 (vol/vol) MeCN-trifluoroacetic acid.…”
Section: Animalsmentioning
confidence: 99%
“…28 Brown et al (2001) examined the effeets of sibutramine on feeding and body weight in a rat model of dietary obesity. Male Wistar rats were conditioned to a reversed phase lighting 12:12-h light-dark eycle with lights on at 03h00.…”
Section: 24-sibutrarnine Food Intake and Macronutrient Selectionmentioning
confidence: 99%
“…Since sibutramine is a relatively new dmg, most studies to date have focused on its effectiveness in promoting and sustaining weight-loss in both the animal and human model (Jackson et al, 1997a(Jackson et al, , 1997bDay & Bailey, 1998;Grignaschi, et al, 1999;Brown et al, 2001;Strack et al, 2002). Only two human trials have examined sibutramine's possible effects on macronutrient selection but their results are inconclusive (RoUs et al, 1998;Chapelot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%